2018
DOI: 10.1101/405290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two key events associated with a transposable element burst occurred during rice domestication

Abstract: 21produced the components necessary for the mPing burst, not the loss of epigenetic 36 regulation. 37 38 39 majority of TE bursts have been inferred after the fact -via computational analysis of 45 whole genome sequence -the stealth features they require for success have remained 46 largely undiscovered. 47Revealing these stealth features requires the identification of a TE in the midst of a 48 burst. This was accomplished for the miniature inverted-repeat transposable element 49 (MITE) mPing from rice 1,2 . M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In addition to differences in the amount of protein expression, significant differences in mPing element copy number are found in different rice cultivars (Chen et al, 2019). We predicted that increased element abundance in the yeast genome would increase the probability Frontiers in Cell and Developmental Biology frontiersin.org of transposition complex formation.…”
Section: Increased Element Copy Number Increases Excision Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to differences in the amount of protein expression, significant differences in mPing element copy number are found in different rice cultivars (Chen et al, 2019). We predicted that increased element abundance in the yeast genome would increase the probability Frontiers in Cell and Developmental Biology frontiersin.org of transposition complex formation.…”
Section: Increased Element Copy Number Increases Excision Frequencymentioning
confidence: 99%
“…mPing is a Miniature Inverted-repeat Transposable Element (MITE) derived from the larger Ping element and is highly active in some rice cultivars (Naito et al, 2006;Naito et al, 2009). The mPing element was shown to increase in copy number during tissue culture treatment (Jiang et al, 2003), and naturally reached hundreds of genomic copies in some rice cultivars (Naito et al, 2006;Naito et al, 2009;Yasuda et al, 2013;Chen et al, 2019). As a non-autonomous element, mPing does not encode ORF1 and TPase proteins, but instead is mobilized by the ORF1 and TPase proteins encoded by the autonomous Ping or Pong elements (Yang et al, 2007;Hancock et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPLITREADER used here (Quadrana et al, 2016) was utilised for a global analysis of LTR-RTs in 602 tomato accessions and TIP-based GWAS (TE-GWAS; TIP-GWAS), that allowed identification of retrotransposon insertions associated with important phenotypic traits, such as flavor (Domıńguez et al, 2020), while insertional polymorphism of class II MITEs in 3,000 rice genomes was analysed using PoPoolationTE2 (Kofler et al, 2016) and TIP-based GWAS showed association of particular MITE copies with MITE copy number, suggesting that MITE subfamilies originate from few "master" copies (Castanera et al, 2021). Another short read based method, RelocaTE2 (Chen et al, 2017) was used to analyse copy number and distribution of mPing, Ping and Pong class II elements actively transposing in rice in 3,000 rice genomes (Chen et al, 2019) and to detect de novo insertions of mPing in 272 rice recombinant inbred lines (RILs) developed from a cross between Nipponbare and HEG4 known to carry active mPing (Chen et al, 2020).…”
Section: Identification Of Novel Insertion Sites Produced By Actively...mentioning
confidence: 99%